External Vulnerability in Emerging Market Economies : How High Liquidity Can Offset Weak Fundamentals and the Effects of Contagion - Mulder, Christian; Bussiere, Matthieu (Washington, D.C. : International Monetary Fund, 1999)
This paper investigates the factors behind the 1994 and 1997 crises and whether these can explain the 1998 crisis. The study reveals that: (i) variables used in an Early Warning System model developed by IMF staff scored well in predicting the 1998 crisis out-of-sample; (ii) all three crisis episodes can be well explained by a parsimonious set of core fundamentals and liquidity related variables; and (iii) the presence of an IMF-supported program significantly reduced the depth of crises. The results suggest that as a rule of thumb countries should hold reserves to the tune of short-term debt to avoid contagion-related crises, provided their current deficits are modest and their real effective exchange rates are not significantly misaligned.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet